Profiling change of direction ability using sub-phase 5-0-5 analysis - Ryan, C.; Uthoff, A.; McKenzie, C.; Cronin, J. (International Journal of Strength and Conditioning, 2022)
Change of direction (COD) ability is an important component for most field and court sport athletes. The modified 5-0-5 COD test is a commonly used test to measure 180-degree COD performance, the diagnostic value of which can be advanced using a multiple-timing light set-up to divide the test into sub-phases. The aim of this research was to determine what proportion of the 5-0-5 COD test was spent performing the 180-degree COD, whether anthropometry and position of the player influenced the sub-phase performance and provide an alternative approach to improve diagnostics for coaches and practitioners. Ten elite female netball athletes participated in this study. Dual beam timing gates set at 0, 2, and 4 m were used to isolate the phases of the 5-0-5 COD test and quantify COD performance. Independent t-tests were used to assess statistical significance (p<0.05) between anthropometry, position, and performance of the sub-phases. Rank-order of sub-phase performance was also conducted to determine individualized performance across phases. The highest percentage of time was spent during the 180-degree turn and reacceleration 1 phase (~23%). Heavier athletes were significantly slower for deceleration (9.26%), 180-degree turn (17.1%), reacceleration 2 (7.32%) and total time (8.68%), however no differences were identified between taller and shorter players. A sub-phase rank order table was used to provide diagnostic and training insights that allow more targeted programming to improve COD performance.